Caspar Voght & Co. correspondence - Caspar Voght & Co.
Letter (1782 December 20) from Caspar Voght & Co., addressed to the Delaware General Assembly, promoting trade between the U.S. and Germany. Includes a printed list of dry goods and hardware available from the firm.
Mercantile firm in Hamburg, Germany.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Delaware. -- General Assembly -- Correspondence; Dry goods -- Germany; Hardware industry -- Germany; Germany -- Commerce -- United States -- History; Hamburg (Germany) -- Commerce; United States -- Commerce -- Germany -- History